Knowledge management systems adoption framework for effective decision making in Libyan Higher Learning Institutions - Oumran, Hanan Mohamed Mouftah (2022)
Knowledge management system (KMS) plays a crucial role in Higher Learning Institutions (HLI) in their overall performance. KMS can hold the key to HLI progress for the institutions to make management or administration decision. KMS should be adopted by HLIs and organizations looking for quality in their services. Previous studies on KMS frameworks, particularly in the developing countries, were devoid of competitiveness pressure, big data and cloud computing factors from environmental context change management, organization readiness for the organizational context and information technology (IT) infrastructure factor in terms of technology context. This study seeks to analyze the applicability of the existing factors associated with KMS adoption that might aid to decision making in HLIs. The KMS plays significant role in providing information that will lead to improve the decision making which in return will improve effectiveness and efficiency of HLI operations. A conceptual framework need to be proposed to examine the effects of factors on KMS adoption that impact decision making among HLIs in Libya, which is a developing country. The framework needs to be comprehensive that includes necessary factors and based on solid theories. Thus, this study identifies the necessary factors that could influence the KMS adoption in HLI, construct, and propose a framework for the adoption of KMS to support the decision-making in HLIs using the Unified Theory of Acceptance and Use of Technology (UTAUT) and the theory of Technology, Organization, and Environment (TOE). Mixed methods approach of quantitative and qualitative are used for data collection. A survey instrument validated by five experts and pilot test with 50 respondents as preliminary technique before actual data collection. A total of 500 questionnaires were distributed through e-mail, and 306 were returned. The quantitative collected data were analyzed using Structural Equation Modelling (SEM) and Smart PLS 3 software to validate the proposed framework. The results showed that the framework index fitness is appropriate. The study revealed that technology, organization, and environment, which are second order factors, were significant and positively influenced the adoption of KMS. The study also showed that KMS is essential and has substantial relation with the decision-making in HLI. The quantitative approach was then succeeded by a qualitative study to verify the KMS adoption framework and to attest the applicability of the framework. The results confirmed the findings obtained from the quantitative study and contributed to enriching the understanding of the adoption of KMS in HLI. This study could help shape the direction of both theoretical and empirical studies on KMS, specifically on adoption, to support decision-making. The study could also help HLI in a proper and effective adoption through the verified proposed framework. The proposed framework provides insight into how KMS adoption can eventually lead to an enhanced HLI decision-making for management or administrative uses. In essence, the study practically contributes to the running of institutions, organizations, and the decisions making by policymakers.